Odpowiedzi

Najlepsza Odpowiedź!
2010-02-24T14:31:07+01:00
2x+6-3y+6=-4
3x+3y+6=4x+2y+12

2x-3y=-4-6-6
3x+3y-4x-2y=12-6

2x+3y=-16
-x+y=6

2x+3y=-16
y=6+x

2x+3(6+x)=-16
y=6+x

2x+18+3x=-16
y=6+x

5x=-16-28
y=6+x

5x=-44/:5
y=6+x

x=-8,8
y=6+(-8,8)

x=-8,8
y= -2,8

Drugiego to niewiem
2010-02-24T14:36:12+01:00
2(x+3)-3(y-2)=-4
3(x+y+2)=2(2x+y+6)

2x+6-3y+6=-4
3x+3y+6=4x+2y+12

2x-3y=-16
-x+y=6
y=x+6
2x-3(x+6)=-16
2x-3x-18=-16
-x=2
x=-2
y=x+6=-2+6=4

(x-2)²+2y=(x+1)²+y-1
2x=3y
y=2/3x
(x-2)²+2(2/3x)=(x+1)²+2/3x-1
x²-4x+4+ 4/3x = x²+2x+1+2/3x-1
-5 1/3x=-4
-16/3x=-4 /* -3/16
x=3/4
y=2/3x= 2/3 * 3/4 = 1/2 = 0,5

(x-2)²-(x+1)²=5y-26
3x+2y=14
x²-4x+4-x²-4x-4=5y-26

-8x-5y=26 / * 2
3x+2y=14 / * 5

-16x-10y=52
15x+10y=70
---------------
-x=122
x=-122
3*(-122)+2y=14
-366+2y=14
2y=380
y=190
x=-122